Systematic review of chewing simulators: Reality and reproducibility of in vitro studies - Soriano-Valero, Sergio (J Clin Exp Dent, 2020)
BACKGROUND: The aim of this systematic review was to analyze the types of human chewing simulator described in scientific literature. MATERIAL AND METHODS: An electronic search was conducted in the databases PubMed, Embase and Scopus. The search strategy included 10 search terms: “in vitro”; “dental materials”; “shear strength”; “fatigue fracture”; “bite force”; “prosthetic materials”; “chewing simulator”; “chewing machine”; “simulated mastication”; and “dental wear simulator.” Two researchers worked independently to assess the titles and abstracts of the articles. The quality of the in vitro trials selected was evaluated by means of the Consolidated Standards of Reporting Trials scale. RESULTS: The electronic search identified 80 articles related to the topic of interest. After reading the full texts, ten works were selected. The articles focused mainly on the design of chewing simulators. Most of them were considered of moderate quality. Regarding the characteristics that an ideal chewing simulator should encompass, the devices described in articles varied greatly in terms of movement, periodontal ligament simulation, force sensors, and the materials tested. CONCLUSIONS: No chewing simulator offers all the characteristics necessary to reproduce human masticatory movements and forces under the humidity and pH conditions of the oral cavity. A simulator that encompasses all these characteristics would make it possible to standardize trials involving simulated mastication. Key words:In vitro, dental materials, dental wear simulator.